Model Tafsir Al-Qur’ān MTA (Majelis Tafsir Al-Qur’ān) di antara Tafsir dan Ideologi - Sunarwoto Sunarwoto (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2012)
This article deals with the Qur’ānic interpretation offered by Majelis Tafsir Al-Qur’ān (MTA). It tries to answer several questions: to what extent MTA has interpreted the Qur’ān, how it fits (or does not fit) with its ambitious claim that it does not offer any kind of Qur’ānic interpretation, and how this interpretation demonstrates the development of MTA’s thought in understanding the Qur’ān. This article reaches the conclusion that, although MTA claims not to interpret the Qur’ān, in fact it has made such a certain degree of interpretation of the Qur’ān. Its puritan ideology seems to have played a considerable role in colouring its Qur’ānic understanding. As a result, the claim that it does not interpret the Qur’ānis not reliable and even tendentious.DOI: 10.15408/ref.v13i2.896